Death, hospitalization, emergency department visits and out-patient visits in patients with heart failure in contemporary practice: results from the prospective Europeam 9069-patient ARIADNE registry. (25th November 2020) - Lund, L.H; Zeymer, U; Clark, A.L; Barrios, V; Damy, T; Drozdz, J; Fonseca, C; Kalus, S; Koch, C; Maggioni, A
Abstract: Background: In Europe, heart failure (HF) is managed in variable settings and frequently in office-based practice. In HF with reduced ejection fraction (HFrEF) there is now extensive evidence based therapy, but implementation is inconsistent, variable and overall inadequate. The Assessment of Real lIfe cAre –Describing EuropeaN hEart failure management (ARIADNE) registry aimed to assess in detail how outpatients with HFrEF are managed in Europe in contemporary practice. Methods: ARIADNE was a prospective non-interventional registry of patients with HFrEF (NYHA class II-IV) treated by office-based cardiologists or selected primary care physicians (recognized as HF specialists) in a real world setting. Patients were enrolled in 687 centres in 17 European countries, and studied at baseline and after 6 and 12 months. Key pre-specified outcomes were deaths, hospitalizations, emergency department visits, and office visits, and their primary reasons. Results: Over 20 months, we enrolled 9069 patients; median age 69 (19–96) years, 24% women, with 30% older than 75 years, 61% NYHA class II, with a median EF 35% (30–40%). Over a median follow-up of 353 (1–631) days, 382 patients (4.3%) died, with 171 cardiovascular deaths (1.9%). The rates of total hospitalizations overall, for HF, and for non-HF cardiovascular reasons were 19.3, 8.1, and 4.8 per 100 patient years, respectively; and rates of emergency department visits overall, for HF reasons, and for non-HF CV reason were 7.7, 1.6, and 1.8, respectively. The number of HF office visits were on average 1.0 per patient. Conclusions: In this large multinational HFrEF registry with detailed data on cause-specific outcomes and health care utilization, incidence of death was low and outpatient HF visits were few, but incidence of HF and CV hospitalization and emergency department visits was high. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Novartis AG, Switzerland